Peculiarities of academic motivation of the students of high medical school - Bondarenko I.M.; Zavizion V.F.; Kyslytsyna V.S.; Aseyev O.I.; Dmytrenko K.O.; Mashtaler V.S.; Kaniyka H.S.; Starushkevych H.F.; Filat T.V.; Khodzhuzh M.I.M. (Medičnì Perspektivi)
Motivation of students is one of the most efficient means of improving process and results of training, and motives being impetus of academic process and qualitative mastering of learning material. Formation of academic motivation today is one of the main tasks of up to date education. Academic motivation depends on individual peculiarities of students, character of the closest referent group, level of development of students’ collective, etc. Aim of the research was 1) studying level of academic motivation of students of SE “Dnipropetrovsk medical academy of HM of Ukraine”; 2) revealing prevailing motives of educational activity of students of high medical establishment; 3) assessment of moral readiness of students to inevitable mistakes in future work; 4) studying dynamics of motivation sphere of future doctors in the course of the studies in high medical school; 5) comparison of motivation and intellectual indices of students of junior, pre-graduate and graduate courses; 6) recommendations for lecturers as for improvement of academic motivation of the students. By means of anonymous testing of 537 students of the first, fifth and sixth courses there were studied peculiarities of academic motivation and intellectual indices of the students. Academic motivation of students at large is sufficiently high. Professional and scientific-cognitive motives of educational activity are the most expressed ones. Communicative motives and those of creative self-realization are somewhat less, social motives and motives of prestige are much less. Rather low indices of failure avoidance testify to moral mood of students to inevitable mistakes in their future work. On the whole, a tendency to academic motivation decreasing in the course of studies was revealed. Expressiveness of academic motivation does not depend on intellectual indices of students.